(7-z)(3z-5)=0

Simple and best practice solution for (7-z)(3z-5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7-z)(3z-5)=0 equation:


Simplifying
(7 + -1z)(3z + -5) = 0

Reorder the terms:
(7 + -1z)(-5 + 3z) = 0

Multiply (7 + -1z) * (-5 + 3z)
(7(-5 + 3z) + -1z * (-5 + 3z)) = 0
((-5 * 7 + 3z * 7) + -1z * (-5 + 3z)) = 0
((-35 + 21z) + -1z * (-5 + 3z)) = 0
(-35 + 21z + (-5 * -1z + 3z * -1z)) = 0
(-35 + 21z + (5z + -3z2)) = 0

Combine like terms: 21z + 5z = 26z
(-35 + 26z + -3z2) = 0

Solving
-35 + 26z + -3z2 = 0

Solving for variable 'z'.

Factor a trinomial.
(-7 + z)(5 + -3z) = 0

Subproblem 1

Set the factor '(-7 + z)' equal to zero and attempt to solve: Simplifying -7 + z = 0 Solving -7 + z = 0 Move all terms containing z to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + z = 0 + 7 Combine like terms: -7 + 7 = 0 0 + z = 0 + 7 z = 0 + 7 Combine like terms: 0 + 7 = 7 z = 7 Simplifying z = 7

Subproblem 2

Set the factor '(5 + -3z)' equal to zero and attempt to solve: Simplifying 5 + -3z = 0 Solving 5 + -3z = 0 Move all terms containing z to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3z = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -3z = 0 + -5 -3z = 0 + -5 Combine like terms: 0 + -5 = -5 -3z = -5 Divide each side by '-3'. z = 1.666666667 Simplifying z = 1.666666667

Solution

z = {7, 1.666666667}

See similar equations:

| 14-5x=-21 | | 4(5z-1)-2(z+5)=3(z+1) | | 2.8=-0.9+y | | 15=6y-3y | | a-3=-20 | | s=3m+3z | | x^4+3x^2=4 | | 9y=-2(y+1) | | 9x-42=2x | | 8y-15y+7= | | -2(-4z)=64 | | 3x+7y= | | 2(5z)=-80 | | 10b^2-8b-7=0 | | x+43=38 | | -11m+6m=11-31 | | -5(3p+4)-25=3(2p+6) | | 2(c-6)=3(c-7) | | 8-6n+2n=43-95 | | 2y-4(2y+4)=-4-2(-1-y) | | 2(0)+6=y | | (2x+4)(5x-6)= | | 29=5-3h | | 4*-3+7= | | 4*-3=7 | | 2(5z-1)-5(z+2)=2(z+1) | | 5+2n-4=5n+2-2n | | -14=-7t | | 10p-11=-2p+7 | | 3.5q-2.7-3.9q=-1.4q-5.2 | | 2(3x-4)-(2x-4)= | | 45-23=x |

Equations solver categories